Efficacy of low power laser therapy in diabetic ulcers (Research, Society and Development, 2021)
Physiotherapy also uses technological resources for the treatment of diabetic foot ulcers, such resources act as modeling of healing. As a physical therapy treatment, low-intensity laser has been highlighted with effectiveness. This study aims to seek scientific evidence on the use of low-intensity laser in diabetic foot ulcers. A systematic literature review, through searches in scientific platforms: Pubmed, SCIELO, LILACS; the following keywords being used: physical therapy; diabetic foot, low power laser therapy; meeting the following criteria: publications in Portuguese and English, year of publication greater than 2010. The analysis of the studies carried out using the PEDro score showed that the results presented high quality evidence. Low-intensity laser increases the expression of growth factors that are capable of inducing extracellular matrix deposition, cell proliferation at the injury site, favoring angiogenesis. The early application of low-power laser on wounds proved to be able to accelerate the process of wound closure, with effects mainly on the inflammatory and proliferative phases. In addition, the laser acts to stimulate a more organized healing process, and has a direct influence on reducing the antalgic process. The present study showed that the use of low-intensity laser used in the treatment of diabetic ulcers in the healing acceleration process obtained results with high quality scientific evidence, taking into account the methods used and the results obtained, however they are still necessary more studies on the subject.